Penggunaan Instrumen Permainan Bendera dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam - Hasan Basri (Universitas Batanghari Jambi, 2020)
Islamic education at the elementary school level is introduced to students about aspects of the Islamic religion itself, getting to know aspects of the pillars of Islam and faith in Allah down to Qadha and Qadar, and studying the Qur'an. In everyday life behave praiseworthy and avoid disgraceful behavior. Introducing and carrying out the pillars of Islam starting from reading two sentences of the creed to knowing the procedures for carrying out the pilgrimage. Telling stories of disgraceful people in everyday life and telling stories of the prophets and providing examples of those stories. Of all that will make the students as provisions later. If it is conveyed in a less conventional way, it will be difficult for students to digest that aspect. Based on the description above, it is necessary to do a study. The aims and objectives of this study are to improve learning outcomes of Islamic Religious Education by using Flag Game Instruments in Islamic studies. This research was conducted in two cycles. In this study, the participants were grade I SDN 182 / IX Ujung Tanjung. The number of students is 29 children. Teacher activity observation sheets, student activities and tests used in the data collection method. To get data on learning outcomes. The results and data obtained from Cycle I and Cycle II emphasize that by using the Flag Game instrument, the results and data obtained from Cycle I and Cycle II state that a very significant increase in learning outcomes is found with a number of good scores and very good scores from those initially only 48.1% to 92.8%.